Establishing the patterns of influence of environmental conditions on the biochemical indicators of grape must and the wine produced from it - Shukurova, Vusala; Huseynov, Movlud; Salimov, Vugar; Gasimova, Afet (Technology audit and production reserves, 2026)
The object of research is grape must and wines made from white and red grape varieties grown in the conditions of the Absheron and Gabala regions. The article provides a comparative analysis of the biochemical indicators of must and wine samples made from grape varieties grown in the ecological and geographical conditions of the Absheron and Gabala regions of Azerbaijan. Grapes of some white (Muscat white, Viognier, Chardonnay, Semillon, Riesling, Bayan Shirey, Rkatsiteli) and red (Aleatico, Shiraz, Merlot, Madrasa) varieties were used as the research material. In order to determine the direction of use and technological suitability of the harvest of the studied grape varieties, the biochemical indicators of must were studied, various wine samples were prepared and their physicochemical analysis was carried out. It was found that the biochemical composition of the must and the physicochemical indicators of wine samples vary depending on the soil and climatic conditions of the place where the grape variety is grown. It turned out that the juice density of grape varieties grown in the Gabala district is 1.09122–1.11207 g/L, and the juice density of grape varieties grown in the Absheron district is higher and is 0.90010–1.90024 g/L. Grape varieties grown in the Gabala district are characterized by a higher content of tartaric acid. The highest content of tartaric acid was noted in the Semillon variety. In grape varieties grown in the Gabala district, the malic acid content varies in the range of 0.3–3.2 g/L, and in varieties grown in the Absheron district, within 0.2–1.2 g/L. The amount of polyphenols in grapes grown in the Gabala district was higher than the similar indicator for the Absheron district. The obtained results can be used in the winemaking industry, which will allow producers to more accurately select raw materials for the production of a specific type of wine, and can also be useful for winemakers in other regions with similar soil and climatic conditions and the assortment of regionalized varieties.